2013
DOI: 10.3109/08880018.2013.763391
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Chemotherapy on Dental Status of Children Cancer Survivors

Abstract: According to our examination dental status of long-term survivors is worse than in controls. Hence proper oral hygiene for children cancer survivors (CCS) is critical. In order to meet the need for dental care in CCS health authorities are encouraged to revitalize the dental services Long-term follow-up of CCS is necessary to monitor their dental growth and oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 23 publications
3
45
0
8
Order By: Relevance
“…Sin embargo, existen algunos tipos de cáncer en los cuales su magnitud afecta a grupos más jóvenes. La casuística en las personas de menos edad, especialmente los menores de 30 años, es muy escasa 11 . En el estudio se seleccionó una muestra de 50 participantes considerando la incidencia y los criterios de inclusión.…”
Section: Discussionunclassified
“…Sin embargo, existen algunos tipos de cáncer en los cuales su magnitud afecta a grupos más jóvenes. La casuística en las personas de menos edad, especialmente los menores de 30 años, es muy escasa 11 . En el estudio se seleccionó una muestra de 50 participantes considerando la incidencia y los criterios de inclusión.…”
Section: Discussionunclassified
“…2 It is found that the ALL children are at the higher risk of tooth decay than the healthy group; and the root malformations, dental agenesis, microdontia and enamel dysplasia are more common among the children with this disease. 10,11 A study reported the higher rates of dental caries in the ALL children than the normal population. 12 It is shown the oral hygiene status in the ALL children in different phases of treatment and found that the DMFT/DMFT indices were much further during the maintenance phase than other phases in.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…A quimioterapia foi o tratamento antineoplásico mais prevalente na presente pesquisa, contabilizando 50 pacientes, também sendo mencionado, em vários estudos, como o principal tratamento para o câncer (ALBERTH et al, 2004;AVŞAR et al, 2007;HONG et al, 2010;NEMETH et al, 2013 Os dentes possuem muitas propriedades físico-quimicas que desempenham funções especificas, como as de proteção da estrutura dentaria, diluição de substancias acidas erosivas na cavidade oral por meio do fluxo salivar, neutralização e tamponamento dos ácidos pelo ph e também o fornecimento de íon de cálcio e fosfato, agindo assim contra a erosão dentária. (SHITSUKA, 2018).…”
Section: Análise Das Condições Bucaisunclassified
“…A quimioterapia é o tratamento antineoplásico mais prescrito para os pacientes da pesquisa e também descrito na literatura como principal tratamento para o câncer (CHO, 2010;HONG, 2010;NEMETH, 2013 biofilme dental e que, segundo Pereira (2009), quando associado a uma dieta rica em carboidratos pode contribuir para o aumento da prevalência da doença cárie dentária.…”
Section: Análise Das Condições Bucaisunclassified